Improving the Utilization of Oil Palm Fronds Through Nitrogen Supplementation in Dairy Goats - Nhupien, Pramote Paengkoum (2003)
The high cost of supplementing poor quality roughage-based diets with imported protein concentrates for ruminants deserves attention in seeking cheaper alternatives. The purpose of the thesis was to determine the amount and type of nitrogen (N) sources, particularly the use of local protein foliages to enhance rumen ecology thus improving performance of dairy goats fed oil palm fronds (OPF). Based on the above objectives, five experiments were conducted. Experiment 1 investigated the nutritional value and degradability of untreated oil palm fronds (O-OPF) and compared to steamed (S-OPF) and pre-pelleted and steamed OPF (PSOPF). Dry matter (DM) and organic matter (OM) degradability of OPF subjected to steam treatment (S-OPF and PS-OPF) were higher (P<0.05) than the untreated OPF. Experiment 2, investigated the optimum level of fermentable N (urea) supplementation to optimize the use of S-OPF by weaner goats. Five male Saanen goats of 4-6 months old and an average body weight (BW) of 21.4 ± 1.6 kg were used in a 5 x 5 Latin square experiment. The diet treatments were five levels of urea viz, 10, 20, 30, 40 and 50 g urea/kg of steamed OPF. Dry matter intake (OMI), nutrients digestibility, products of rumen fermentation, microbial N supply, N absorption and retention increased (P<0.05) with the addition of urea up to 30 g/kg OPF, and thereafter decreased (P<0.05) with increased urea supplementation. This implied that the optimal level of urea supplementation in a sole OPF diet was 30 g urea/kg steamed OPF. The hypothesis that addition of fermentable energy will enhance the use of urea higher than 3% in OPF diet was validated in Experiment 3. Twelve Saanen goats aged between 5 to 6 months and BW of 23.4 ± 1.6 kg were used in a 2 x 3 Factorial arrangement of randomized complete block design. Factors were three levels of urea (3,4 and 5%) and two levels of energy supplemented with cassava waste [low energy (LE) or high energy (HE)]. On the average, all production parameters measured were higher for HE as compared to LE diets. Nevertheless, the optimal level of urea supplementation remained at 3% in both diets.